STRATEGI SEKOLAH DALAM MENGHADAPI SISTEM ZONASI STUDI DI SMP NEGERI 3 MREBET PURBALINGGA - Asep Henry Habibullah (CV. Amerta Media, 2019)
The zoning program is one of the government programs in the framework of equalizing the quality of education. Through this program schools can compete to have good quality and are not inferior to schools that are already considered favorites. This program provides broadest access for schools and students to develop their quality. But in its implementation, the policy is inseparable from the pros and cons. There are schools that benefit and are disadvantaged. Thus, schools must have strategies in dealing with the school zoning system. The results of research at SMP N 3 Mrebet Purbalingga, the school's strategy in dealing with the zoning system, are a) building school branding; b)